Changes in consumption behavior in Mexico in relation to exercise, mental health and diet during the COVID-19 confinement (Revista de Investigaciones Universidad del Quindío, 2023)
The impact of COVID-19 was felt immediately, due to the widespread lockdown and social distancing measures taken by all governments globally; manifesting different attitudes taken by people during confinement, the research aims to know if there are differences in the behavior of Mexican men and women specifically in relation to psychological factors such as exercise and mental health and cultural factors specifically regarding the diet that people had during a period of confinement due to COVID-19. A descriptive research was carried out with a quantitative approach, to a sample of 1007 subjects nationwide, 64% women and 36% men. Data analysis was done using the SPSS version 25 statistical package. For the descriptive analysis, each of the attitudinal phrases of the instrument that were evaluated under a Likert scale were taken, nested under the top two box and bottom two method, thus obtaining an ordinal scale variable. To verify the hypotheses, an analysis of variances was carried out, as well as a correlation analysis (Pearson). The study reveals that the daily coexistence to which individuals were subjected due to the isolation produced by the COVID-19 pandemic, has caused both men and women to have similar behaviors, modifying their consumption habits, in order to improve health and stay physically and mentally healthy, it can not be predicted if these behaviors will persist when the pandemic has ended and people return to their daily activities outside the home but yes, it gives a vision of how people have adapted to this situation.
Keywords: Consumer behavior; consumer behavior COVID-19; effect of pandemic behavior; activities in confinement